Pengaruh Perilaku Organisasi terhadap Kepuasan Kerja Tenaga Kependidikan di Sma Fransiskus 2 Jakarta - Siagian, Siagian; Baginda Edward; Murniarti, Murniarti; Erni, Erni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of Organizational Behavior (OB) on Job Satisfaction of Education Personnel at SMA Fransiskus 2 Jakarta through a synthesis of the dimensions of organizational communication, leadership, work culture, motivation, and professional development. The research method used was a literature review with a qualitative approach, through the collection and analysis of scientific journals published between 2021 and 2025 that are relevant to the variables of Organizational Behavior and Job Satisfaction in educational settings. The results indicate that Organizational Behavior has a significant and multidimensional influence on Job Satisfaction, with organizational communication and work climate being the main foundations for building trust and reducing role conflict; supportive leadership, career development, and work motivation are strong predictors of extrinsic satisfaction and commitment; and support for professionalism and competence increases intrinsic satisfaction through pride and self-efficacy. The conclusion of this study confirms that the more effective, fair, and supportive the implementation of OB, the higher the level of Job Satisfaction of Education Personnel, which positively impacts performance, loyalty, and school operational stability. Keywords: Organizational Behavior, Job Satisfaction, Educational Personnel, Organizational Communication